2019
DOI: 10.1177/1729881419862733
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive formation control of quadcopters based on a leader–follower approach

Abstract: The formation control problem for multi-agent systems has been explored in recent years. However, controlling a formation of multiple aerial vehicles in the presence of disturbances has been a challenge for control researchers. To deal with this issue, a robust adaptive formation control algorithm for a group of multiple quadcopters is proposed. A nonlinear model of the dynamics of the formation error is obtained based on a leader-follower scheme. This model considers both the relative position in the x-y plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In this section, we briefly present the quadrotor dynamics model, as it was clearly introduced and verified in many previous studies [34,43,50,51]. Figure 1 illustrates the quadrotor configuration.…”
Section: Quadrotor Dynamics Model and Problem Formulationmentioning
confidence: 95%
“…In this section, we briefly present the quadrotor dynamics model, as it was clearly introduced and verified in many previous studies [34,43,50,51]. Figure 1 illustrates the quadrotor configuration.…”
Section: Quadrotor Dynamics Model and Problem Formulationmentioning
confidence: 95%
“…Quadcopters, which are one of the most active classes of UAVs, have two pairs of motors to adjust their altitude and attitude. The reasons why quadcopters have been widely researched in many recent studies are that their practical models shrink in experiments for safety, and they have enough actuators to control their rigid body states including position and orientation [33][34][35][36]. In considering the formation control of multiple quadcopters, each agent can be treated as a point-mass system, and the outer loop dynamic model is described as a second-order dynamics.…”
Section: Application To Multiple Quadcopter Systemsmentioning
confidence: 99%
“…The goal there is to establish consensus protocols for the design of distributed controllers for a group of dynamic agents such that the network reaches an agreement of certain quantity of interest that depends on the states of all agents. Thereupon, consensus has become a comprehensive interdisciplinary subject where it addresses several research topics such as finite-time consensus for networks of dynamic agents [1], [2] networks with fixed topologies [3] networks with switching topologies [4], formation control [5], [6], and asynchronous consensus [7]. Examples of pioneering results in the field are, the Vicsek model [8], which considered a decentralised control approach and showed that alignment can be achieved through the heading of each agent, and the work by Jadbabaie [9], which provided a detailed mathematical proof of the Vicsek model and presented the jointly connected condition for networks with switching topology.…”
Section: Introductionmentioning
confidence: 99%